Evaluation of a concentrated parameters mathematical model applied to drying of yerba mate leaves with variable mass transfer coefficient. (25th July 2016) - Pilatti, Daniel; Johann, Gracielle; Palú, Fernando; da Silva, Edson Antonio
Highlights: Experimentally and numerically fixed bed drying characteristics of mate leaves. Development of a phenomenological model with variable mass transfer coefficient. The model predicted accurately the moisture profile. Abstract: In this study, fixed bed drying characteristics of yerba mate leaves were investigated experimentally and numerically, in a convective drier, on the drying air conditions at temperatures of 55, 65 and 75 °C and 1.0, 1.5 and 2.0 m s −1 . Beyond four simplified mathematical models, selected to describe and compare the drying kinetics of yerba mate, was developed a phenomenological model with variable mass transfer coefficient, dependent on the concentration of water in the yerba mate leaves and air temperature. The fit qualities of the simplified models and the developed model were evaluated by using the determination of coefficient, reduced chi-square, root means square error and Akaike Criterion. The selected simplified models and the developed model described well the drying process, with determination of coefficient, for all simulated drying conditions, values higher than 98%. The moisture diffusivity values varied between 1.037 × 10 −7 and 5.463 × 10 −7 m 2 min −1 .